SOME PROBLEMS AND ISSUES OF SUSTAINABLE MANAGEMENT OF MANGROVE ECOSYSTEMS OF TAMIL NADU, INDIA - Fernando, Olivia J.; Pandian, Ponnammal K. (Journal of Indian Fisheries Association, 2015)
Mangrove forests, which are found along a substantial portion of thecoastlines in the tropics, are fast disappearing by reclamation for aquaculture,farming, residential and industrial development and non-sustainableharvesting of timber. They play an important role in supporting tropicalestuarine and coastal food webs, by providing a major source of organicmaterial and acting as nursery grounds and habitats for commerciallyimportant fish species. For a variety of reasons relating to human activities,large areas of mangrove forests are being lost or threatened with disruption.Mangrove, a tidal wetland, is a good example of complex land and watersystem whose resource attributesÂ· is neither fully understood from anecological perspective nor valued comprehensively in economic terms. Withincreased ecological and social perception of the functions of wetlands, theutility and relative values will increase. The perception, however, variesfrom society to society. It must be recognized that mangrove forests differgreatly in local conditions and in their ability to produce a wide variety ofeconomic products. What may be highly productive strategy for one countrymay have little meaning to its neighbour. Therefore, it becomes essentialthat from among diversity of potential uses of the mangrove environment,specific uses will have to be decided, and management plan developed onsite, or area specific basis.It is therefore necessary to arrive at a balance between the views of theecologists and economists on the management of mangroves. Biologicalconservation should encompass resource management in the sense thatintegrity of the biological and physical attributes of the resource base shouldbe sustained and man-induced management practices should not alter anecosystem to the extent that biological production is eliminated. Sustainedyield management for food, fiber and fuel would serve to sustain local fisherieswhile generating new economic enterprises. This requires the recognition ofmangrove environment as a resource with economic value, and managedaccording to local conditions and national priorities.Keywords: Mangrove ecosystem, Sustainable Management